2014
DOI: 10.4103/0019-5049.147138
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peripheral nerve stimulator versus ultrasonography guided axillary block using multiple injection technique

Abstract: Background:The established methods of nerve location were based on either proper motor response on nerve stimulation (NS) or ultrasound guidance. In this prospective, randomised, observer-blinded study, we compared ultrasound guidance with NS for axillary brachial plexus block using 0.5% bupivacaine with the multiple injection techniques.Methods:A total of 120 patients receiving axillary brachial plexus block with 0.5% bupivacaine, using a multiple injection technique, were randomly allocated to receive either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…19 Axillary blocks with US guidance exhibited similar success rates and complication rates as NS guidance. 20 Our study demonstrated the feasibility of a BPB rat model and confirmed the efficacy and safety of BPB under NS-guided conditions. Further studies should be performed to investigate the US-guided BPB model in rats and to compare US and NS guided-BPB in rats for the development of a safer and more convenient BPB method.…”
Section: Discussionsupporting
confidence: 69%
“…19 Axillary blocks with US guidance exhibited similar success rates and complication rates as NS guidance. 20 Our study demonstrated the feasibility of a BPB rat model and confirmed the efficacy and safety of BPB under NS-guided conditions. Further studies should be performed to investigate the US-guided BPB model in rats and to compare US and NS guided-BPB in rats for the development of a safer and more convenient BPB method.…”
Section: Discussionsupporting
confidence: 69%
“…With the development of ultrasound technology, there is an increase in the success rate, shorter onset time, and decrease in the volume required for successful ABPB. [17]…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasound-guided peripheral nerve blockade techniques ( Kapral et al., 1994 ) have several advantages for patients undergoing trauma surgery with infrequent complications ( Kettner et al., 2011 ; Neal, 2016 ). The variations of nerve structures can be visualized by sonography reducing the volume needed to achieve complete nerve blockade ( Harper et al., 2010 ; Riazi et al., 2008 ) with a high success rate ( Chan et al., 2007 ; Jochum et al., 2013 ; Kumar et al., 2014 ). Smaller doses of local anesthetics are associated with incomplete nerve blockades ( Barrington and Kluger, 2013 ), while higher doses are not recommended because of the potential risk of local anesthetic systemic toxicity ( Neal et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%